Melatonin-regulated heat shock proteins and mitochondrial ATP synthase induce drought tolerance through sustaining ROS homeostasis in H2S-dependent manner - Khan, M Nasir (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.